2000
DOI: 10.3758/bf03212136
|View full text |Cite
|
Sign up to set email alerts
|

Partial orientation pop-out helps difficult search for orientation

Abstract: Weinterrupted pop-out search before it produced a detection response by adding extra distractors to the search display. Weshow that when pop-out for an orientation target fails because of this interruption, it nevertheless provides useful information to the processes responsible for difficult search. That is, partial pop-out assists difficult search. This interaction has also been found for color stimuli (Olds, Cowan, & Jolicoeur, 2000a, 2000b. These results indicate that interactions and/or overlap between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Friedman‐Hill & Wolfe, ). Guidance (Olds, Cowan, & Jolicoeur, ,b,c) or preview of features in a target conjunction (Olds & Fockler, ) also facilitates search for complex targets. One set of results has shown evidence for linguistic guidance.…”
Section: Visual Properties and Distractors In Reference Production Anmentioning
confidence: 99%
“…Friedman‐Hill & Wolfe, ). Guidance (Olds, Cowan, & Jolicoeur, ,b,c) or preview of features in a target conjunction (Olds & Fockler, ) also facilitates search for complex targets. One set of results has shown evidence for linguistic guidance.…”
Section: Visual Properties and Distractors In Reference Production Anmentioning
confidence: 99%
“…On a much broader time scale than that used in Olds et al's (2000aOlds et al's ( , 2000b experiments, Humphreys (1997, 2002) presented one set of colored distractors for a full second before adding to the display a set of different-colored distractors plus the target. They found that participants seemed to remember which distractors had already been discarded as nontargets during that initial second and thus were able to locate the target very efficiently.…”
mentioning
confidence: 99%
“…This process can be facilitated by at least two kinds of help-search assistance and visual marking-that seem to work by narrowing down the set of locations at which the target might be found. For example, in the experiments conducted by Olds et al (2000aOlds et al ( , 2000b and Humphreys (1997, 2002), the visual display was incrementally delivered, providing information about locations that no longer needed to be considered and narrowing the search through a restriction in the number of relevant locations.…”
mentioning
confidence: 99%
“…According to the biased competition framework, the apparent dichotomy between serial and parallel search processes may not be the result of two separate mechanisms (eg preattentive parallel visual feature extraction followed by a serial attentional spotlight), but rather the product of a single parallel competitive process. This single process is supported by observations of improvement in visual search tasks better described by a graded enhancement of feature salience (Duncan & Humphreys, 1989;Olds, Cowan, & Jolicoeur, 2000a, 2000b, 2000c. Olds et al (2000aOlds et al ( , 2000bOlds et al ( , 2000c presented single-feature visual search pop-out displays for very brief periods of time, less than 100 ms in some conditions, before changing them to conjunction-search displays.…”
Section: Introductionmentioning
confidence: 70%